Celulose: efeitos estruturais de sua modificação por química de superfícies - Daniel, Eduardo Mendes (Universidade Federal de São Carlos, 2025)
Cellulose, the most abundant biopolymer on the planet, exhibits great versatility for chemical modifications. This work aimed to investigate the structural effects arising from the chemical surface modification of kraft pulp cellulose, correlating microstructural changes with the macroscopic properties of derived cryogels. To this end, cellulose was functionalized via two distinct routes: anionization, through TEMPO ((2,2,6,6-tetrametil-piperidi-1-nil)oxil) oxidation, and cationization, through etherification with GTMAC (Glycidyltrimethylammonium chloride). The success of the reactions was confirmed by Infrared Spectroscopy (FTIR), which detected the carboxylate band in the TEMPO samples and changes in the ether region 1030 − 1163cm−1 in the GTMAC samples, and by Zeta Potential measurements, which validated the change in surface charges. X-Ray Diffraction (XRD) indicated that both surface modifications, in general, increased the material’s crystallinity index. Atomic Force Microscopy (AFM) revealed distinct morphologies, such as aggregated nanofibers in GTMAC1 and a more defined fibrillar structure in TEMPO1. The produced cryogels were analyzed by Scanning Electron Microscopy (SEM) and compression tests. Notably, the GTMAC2 and TEMPO1 samples exhibited the three characteristic compression regimes of stable foams, whereas GTMAC1 and TEMPO2 failed in this regard. Additionally, the GTMAC1 sample demonstrated the highest water percolation rate. The results establish a direct correlation between the type and degree of cellulose surface functionalization and the structural and mechanical properties of the resulting cryogels.
Cellulose: structural effects of surface chemical modification
Keywords: Celulose; Criogéis; Espumas; Funcionalização; Cellulose; Criogels; Foams; Functionalization; CIENCIAS EXATAS E DA TERRA::MATEMATICA; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::POLIMEROS E COLOIDES; 9. Indústria, Inovação e Infraestrutura; 13. Ação contra a Mudança Global do Clima